MENGURAI POTENSI RUANG PUBLIK LEMBAGA PENYIARAN PUBLIK DALAM UPAYA DEMOKRATISASI MASYARAKAT LOKAL - Rochmad Effendy (REFORMASI, 2014)
2014 Presidential Election coverage on private broadcasters were biased toward any presidential candidate. Shades of biased coverage of private broadcasters are still visible even after the presidential election. The hope of obtaining quality news and editorial independence is hard to acquire for people who crave for balanced news and quality journalism. As such, they felt embarrassed by the broadcast program content of private broadcasters who provide low taste programming which dampen their quality cultural appreciation. This is due to the fact that the broadcast program content is designed to meet the tastes of the people’s majority regardless of their cultural, social, ethnic, religious diversity. The profit making impetus underlying private broadcasters operation has increasingly made them even powerless due to absence of space to participate in the supervision and management of the broadcast programming. Interestingly, those weaknesses of the private broadcasting performance can be met by the public broadcaster. This paper will discuss the public broadcasting potentials as an ideal public sphere which enables them to develop their social capital as well as an arena for further strengthening of civil society that will help smooth the process of democratization. An understanding of the essence of public broadcasting by civil society member is more urgent as the newly drafted bill on Indonesia Radio and Television Public Broadcasting (RTRI) are being prepared by parliament.